Respiratory Syncytial Virus Infection: Its Propensity for Bacterial Coinfection and Related Mortality in Elderly Adults. (12th November 2020) - Godefroy, Raphael; Giraud-gatineau, Audrey; Jimeno, Marie-Thérèse; Edouard, Sophie; Meddeb, Line; Zandotti, Christine; Chaudet, Hervé; Colson, Philippe; Raoult, Didier; Cassir, Nadim
Abstract: Respiratory syncytial virus (RSV) is an increasingly recognized cause of acute respiratory infection (ARI) in adults. We compared the crude in-hospital mortality of patients with RSV infection alone with that of patients with RSV–bacterial coinfection. Overall, 12  144 hospitalized patients with ARI were screened for RSV detection by polymerase chain reaction between February 2014 and April 2019. In total, 701 (5.8%) had a positive RSV result, including 85 (12.1%) with bacterial coinfection. RSV–bacterial coinfection was associated with an increase in crude in-hospital mortality in patients >65 years old (hazard ratio, 2.94; 95% CI, 1.30–6.60; P  = .010). Optimized prevention and management strategies to reduce this burden are needed.